Integrasi Nilai Siri’ na Pacce dalam Pendidikan Islam Sebagai Penguatan Karakter Peserta Didik di Sulawesi Selatan - Nur Amalia; Idrus L (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
This study is motivated by the importance of strengthening students’ character through the integration of local cultural values in Islamic education. The aim of this research is to explore the integration of Siri’ na Pacce values in learning to develop noble character in line with Islamic teachings and local culture in South Sulawesi. The method used is a descriptive qualitative approach through literature study and field context analysis, with data collected from document review, interviews, and observations. The results show that Siri’ na Pacce values effectively enhance empathy, honesty, discipline, and social responsibility among students. The integration is carried out through Islamic education learning, teacher role modeling, and attitude-based evaluation through observation. In conclusion, local cultural values play a significant role in strengthening character education when integrated contextually into the learning process, supported by collaboration among schools, families, and the wider community.